THE USE OF LINGUISTIC MODALITY AMONG MALAYSIAN LECTURERS IN LANGUAGE EDUCATION CLASSROOM FOR TEACHER CANDIDATES - Von, Wong Yee (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study investigates the use of linguistic modality by Malaysian educators within the context of teaching English as a Second Language (TESL) programmes, focusing on its impact on teacher education and the engagement of prospective teachers. Six classroom observations and corresponding audio recordings were analysed using mixed-method content analysis to identify the frequencies and contexts of modal expressions. The findings revealed a predominant use of modalisation with high probability and a balanced modulation of obligation, alongside a notable use of low-inclination modalities. The lecturers used high-probability modal verbs to convey authority and certainty, while strategically using lower-probability modals to enhance engagement and promote critical thinking. Furthermore, the use of Malay modal expressions contributed to inclusivity and linguistic adaptability in the classroom. These results demonstrated the critical role of modality by educators in shaping the pedagogical communication of prospective teachers. The study highlights the essential need for educators to adeptly manage language choices to meet diverse educational needs and cultural contexts, thus improving teaching strategies in multilingual settings.